Safety analysis of super-critical water reactors – a review - Rowinski, Marcin Karol (2020)
In this paper the authors present the review of numerous Super-Critical Water Reactors (SCWRs) designs currently under development all over the world. The current Generation III/III + nuclear reactors operate with working fluid under subcritical conditions (below Tcr = 374 °C, pcr = 22.115 MPa). The efficiency, limited by the ratio of source and sink temperatures, is low due to operating below the critical temperature. The SCWRs are able to rise efficiency limit while operating at the supercritical conditions. The amount of energy carried by working fluid is higher leading to potential efficiency improvement of nearly 30% above current nuclear stations. Therefore, SCWRs are promising advanced nuclear systems and one of the most interesting Generation IV nuclear reactor technology, as a direct upgrade from Gen III light water reactors (LWRs). The SCWRs are a natural evolution of the LWRs just like it happened in conventional thermal power plants years ago. However, the evolution must be done ensuring safe operation during normal and accidental conditions. The more compact size makes it possible to be used for marine applications such as propulsion system or floating nuclear power plant. Therefore, review of safety analysis has been prepared based on different reactors designs and approaches found in the literature. It was found that the conceptual designs are suitable for deployment and satisfy the design-basis safety criteria. The Japanese investigation is the most advanced one, especially the safety analysis is nearly done. Many possible evaluations of transient and accident condition had been conducted. The other teams are usually limited to ensure safety and stability during normal operating conditions.